Electrotransfer of plasmid DNA radiosensitizes B16F10 tumors through activation of immune response - Savarin, Monika (Radiol Oncol, 2017)
BACKGROUND: Tumor irradiation combined with adjuvant treatments, either vascular targeted or immunomodulatory, is under intense investigation. Gene electrotransfer of therapeutic genes is one of these approaches. The aim of this study was to determine, whether gene electrotransfer of plasmid encoding shRNA for silencing endoglin, with vascular targeted effectiveness, can radiosensitize melanoma B16F10 tumors. MATERIALS AND METHODS: The murine melanoma B16F10 tumors, growing on the back of C57Bl/6 mice, were treated by triple gene electrotransfer and irradiation. The antitumor effect was evaluated by determination of tumor growth delay and proportion of tumor free mice. Furthermore, histological analysis of tumors (necrosis, apoptosis, proliferation, vascularization, presence of hypoxia and infiltration of immune cells,) was used to evaluate the therapeutic mechanisms. RESULTS: Gene electrotransfer of plasmid silencing endoglin predominantly indicated vascular targeted effects of the therapy, since significant tumor growth delay and 44% of tumor free mice were obtained. In addition, irradiation had minor effects on radioresistant melanoma, with 11% of mice tumor free. The combined treatment resulted in excellent effectiveness with 88% of mice tumor free, with more than half resistant to secondary tumor challenge, which was observed also with the plasmid devoid of the therapeutic gene. Histological analysis of tumors in the combined treatment group, demonstrated similar mode of action of the gene electrotransfer of plasmid encoding shRNA for silencing endoglin and devoid of it, both through the induction of an immune response. CONCLUSIONS: The results of this study indicate that irradiation can in radioresistant melanoma tumors, by release of tumor associated antigens, serve as activator of the immune response, besides directly affecting tumor cells and vasculature. The primed antitumor immune response can be further boosted by gene electrotransfer of plasmid, regardless of presence of the therapeutic gene, which was confirmed by the high radiosensitization, resulting in prolonged tumor growth delay and 89% of tumor free mice that were up to 63% resistant to secondary challenge of tumor. In addition, gene electrotransfer of therapeutic plasmid for silencing endoglin has also a direct effect on tumor vasculature and tumors cells; however in combination with radiotherapy this effect was masked by pronounced immune response.